2021
DOI: 10.3390/app11114727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Learning-Based Automatic Floor Plan Analysis Technology: An AHP-Based Assessment

Abstract: This study proposes a technology that allows automatic extraction of vectorized indoor spatial information from raster images of floor plans. Automatic reconstruction of indoor spaces from floor plans is based on a deep learning algorithm, which trains on scanned floor plan images and extracts critical indoor elements such as room structures, junctions, walls, and openings. The newly developed technology proposed herein can handle complicated floor plans which could not be automatically extracted by previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The demand for indoor spatial information is increasing, and automatic floor plan analysis is gaining more attention as an affordable means of acquiring indoor spatial information [2][3][4]. In this context, this study presents a patch-based deep learning network and a framework for reconstructing indoor space for more complex and large-scale buildings as compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The demand for indoor spatial information is increasing, and automatic floor plan analysis is gaining more attention as an affordable means of acquiring indoor spatial information [2][3][4]. In this context, this study presents a patch-based deep learning network and a framework for reconstructing indoor space for more complex and large-scale buildings as compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the high demand for vectorized indoor spatial information, studies on automatic floor plan analysis (i.e., automatically extracting indoor spatial information from floor plan images) have been recently proposed. Floor plans are a good source of indoor spatial information because they are easy to acquire and the automatic techniques based on floor plans are relatively affordable compared to other methods such as light detection and ranging (LiDAR) or manual digitalization [1][2][3]. In fact, a recent study by Kim [3] demonstrated that automatic floor plan analysis technology is more effective in terms of substitutability, completeness, supply, and demand than manual digitalization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extraction of architectural features has been extensively researched [9][10][11][12]. Hence, for training a model detecting walls and other architectural structures in 2D plans, largescale open-source data sets are already available [13]. In contrast, the detection of emergency symbols on plans supported by object detection has not yet been investigated, and no open-source data set with emergency floor plans is available.…”
Section: Introductionmentioning
confidence: 99%